1973
DOI: 10.1159/000240587
|View full text |Cite
|
Sign up to set email alerts
|

Late Effects of Perinatal Morphine Administration on Pituitary-Thyroidal and Gonadal Function

Abstract: A brief period of neonatal morphine sulfate (MS) addiction in the rat results in lifelong alterations in some endocrine functions. Some changes, such as decreased growth, are probably the nonspecific result of neonatal malnutrition. Others may be the result of altered hypothalamic pituitary function. When neo-MS rats were studied as adults they tended to have larger pituitary glands containing less TSH. Their thyroid glands were larger when corrected for the smaller body weight. Testicular weights were increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

1974
1974
2006
2006

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
1
6
1
Order By: Relevance
“…The finding of higher serum T4 values in the female Thiouracil rats of our supplemental study suggests a mirror-image of the chronic, mild hypothyroidis~n reported for early-hyperthyroid rats (Eayrs, 1968, 19711, in contradiction to the results by Bakke et al (1970) showing reduced serum T4 concentration in combined male and female groups of rats treated perinatally with propylthiouracil. The absolute Control-Thiouracil differences in our serum thyroid parameters were, however, quite small (though statistically reliable) for the females and nonsignificant (and in the opposite direction ) for the males.…”
Section: Discussioncontrasting
confidence: 78%
“…The finding of higher serum T4 values in the female Thiouracil rats of our supplemental study suggests a mirror-image of the chronic, mild hypothyroidis~n reported for early-hyperthyroid rats (Eayrs, 1968, 19711, in contradiction to the results by Bakke et al (1970) showing reduced serum T4 concentration in combined male and female groups of rats treated perinatally with propylthiouracil. The absolute Control-Thiouracil differences in our serum thyroid parameters were, however, quite small (though statistically reliable) for the females and nonsignificant (and in the opposite direction ) for the males.…”
Section: Discussioncontrasting
confidence: 78%
“…We have previously re ported that neonatal thyrotoxicosis caused delayed puberty in the rat and this could not be duplicated by neonatal food restriction (9). We also have reported on the late effects o f neonatal caloric deprivation in a group o f rats used to compare with the late effects o f neonatal morphine treatment (6). At 110 days o f age both males and females that had been underfed during the neonatal period had a statistically significant reduction in body size and the relative size o f the uteri was increased, as was seen in the present study.…”
Section: Discussionsupporting
confidence: 77%
“…It may, thus, be possible that the effect pattern observed in FLE-displaying tadpoles, enlarged thyroid follicles lined by flat epithelial cells with no alteration in TSHβ mRNA expression, may represent a new steady-state of pituitarythyroid axis function that was established in response to modulating effects on thyroid gland activity and growth earlier during the exposure period. Interestingly, studies in rats and chickens have also shown that early stimulation of the developing thyroid gland by TSH could have long-lasting effects on functioning of thyrocytes and overall follicular architecture leading to persistently enlarged follicles with increased luminal areas and decreased epithelial cell heights (Bakke et al, 1970;Leung and March, 1976). At present, however, it is not known whether the tadpoles exposed to the lower ETU concentrations in our study experienced increased TSH stimulation during early timepoints of the exposure phase that were not covered by endpoint measurements.…”
Section: Discussionmentioning
confidence: 99%